A static and free vibration analysis method for non-prismatic composite beams with a non-uniform flexible shear connection. (August 2019) - Nijgh, Martin Paul; Veljkovic, Milan
Highlights: Easy to use method to assess the structural response of a generic composite beams. The stiffness of tapered composite beams is accurately captured with proposed model. Proposed model predicts the first eigenfrequency with an average deviation of 0.3%. A limited number of beam segments is sufficient for convergence of the results. Abstract: Steel-concrete composite beams are widely used in practice because of their economic cross-section design. As sustainability becomes more and more important in the construction industry, the design of composite beams must be adapted to meet the requirements of the circular economy. This calls for demountability and reusability of the structural components, as well as optimized use of materials, for example by using non-prismatic beams. Linear-elastic design and the (optimized) use of demountable shear connectors are key in the design of reusable composite structures. In this paper, analytical prediction models for the elastic behaviour and the first eigenfrequency of non-prismatic composite beams with non-uniform shear connector arrangements are derived. The approach is based on 6 th and 2 nd order differential equations used to define matrix equations for a finite number of linearized composite beam segments. The analytical models are validated using experimental and numerical results obtained with a simply supported tapered composite beam. The analytical models are suitable for comprehensive structural analysis of non-prismatic composite beams with non-uniform shear connection.